ИСТОРИЯ ИССЛЕДОВАНИЯ АШУГСКОЙ СРЕДЫ АГБАБА-ЧЫЛДЫР - Автандил, Агбаба (Eurasian Journal of Philology Science and Education, 2015)
One of the reach branches of Azerbaijan ashuq creative work Agbaba-Childir ashuq environment – were researched not only in Azerbaijan, but also in Turkey. In this article looked through work of well – known Turkish scientist Fuad Koprulu like folklore collector, ways of researching of ancient ashuqenvironment, masters of saz and word of Agbaba-Childir’s ashuq environment.